Chromatic Number of the Corona Product of Complete Graph and Star Graph - Asmarani, Mustika; Yulianti, Kartika; Mulyaning Asih, Endang Cahya (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2025)
In this paper, we determine the chromatic number of the corona product of complete graph $K_n$ and star graph $K_{1,m}$. Determination of the chromatic numbers is done by observing patterns, constructing conjectures, and proving them formally. We found that the chromatic number of the corona product of complete graph $K_n$ and star graph $K_{1,m}$ is $\chi\left(K_n\odot K_{1,m}\right)=\left\{\begin{matrix}3,\ \ n=1,2\\n,\ n=3,4,\ldots,\ k\\\end{matrix}\right.$, and the chromatic number of the corona product of star graph $K_{1,m}$ and complete graph $K_n$ is $\chi\left(K_{1,m}\odot K_n\right)=n+1,\ n=1,2,\ldots,\ k$. Furthermore, using Matlab software, a program is created to visualize the coloring of the vertices based on the formula that has been obtained.